THE ANNA LEONOWENS' ANXIETIES AND EGO DEFENSE MECHANISMS AS FOUND IN ELIZABETH HAND'S ANNA AND THE KING: A FREUDIAN PSYCHOANALYTICAL APPROACH - Gampang Nurtjahyo (Universitas Islam Sultan Agung, 2016)
All situations which threat individual’s comfort can be assumed or considered creating an anxiety. All conflicts, disappointment and feeling of frustration which obstruct individual’s progress to reach achievement are also considered as source of anxiety. The threat as it is mentioned can be psychological and physical threats, psychological pressure that all can cause anxiety. There are some ways that can be done by individual to cope with his/her anxiety through some ego defense mechanisms.This reserach is intended to find out Anna Leonowen’s anxieties and her ego defense mechanism toward what happens to her during her career as a royal governess in Siam Kingdom. Freudian psycoanalytical approach is chosen in order to explore the main character’s personalities.